Renal imaging in children with chronic kidney disease - Wiwit Rahmawati; Heru Muryawan; Farah Prabowo (Indonesian Pediatric Society, 2013)
Background Chronic kidney failure is a cause of death inchildren. Diagnosing chronic kidney disease is often made byclinical manifestations, laboratory findings and ultrasonographyor other imaging tests. Early detection of chronic kidney diseaseis needed for education and management of the disease.Objective To describe renal imaging findings and mortality inchildren with chronic kidney disease .Methods This was a cross-sectional study on children with kidneydiseases who were inpatients at Dr. Kariadi Hospital from January2008 to June 2011. Data were taken from medical records. Chronickidney disease was confirmed by clinical manifestations, laboratoryfindings, and radiologic imaging. Renal ultrasound findings weredetermined by the radiologist responsible at that time. Resultswere presented as ft:equency distributions.Results Of 37 chronic kidney disease cases, 27 were males and 10were females. Subjects' most common complaints were dyspnea (7out of 3 7) and edema (30 out of 3 7) . Renal ultrasound imaging ofsubjects with chronic kidney disease yielded the following findings:reduced cortico-medullary differentiation (30 out of 3 7), bilateralechogenic kidneys (21 out of 3 7), reduced renal cortex thickness(4 out of 37) and small-sized kidneys (4 out of 37) . Eight of the37 children died. These 8 subjects had the following radiologicimaging findin gs: both kidneys appeared small in size (4 out ofS),reduced 'renal cortex' thickness (4 out of 8), echogenic kidneys(6 out of 8), and reduced cortico-medullary differentiation (8out of8).Conclusion Renal ultrasound imaging of pediatric subjects withchronic kidney disease revealed findings of reduced corticomedullarydifferentiation, bilateral echogenic kidneys, reducedrenal cortex thickness, and small kidneys bilaterally.